Triathlon as a form of sports consumption: Motives for participation - Malchrowicz-Mośko, Ewa; Młodzik, Maciej; Banio, Adrianna; Omorczyk, Adam (Turyzm/Tourism, 2018)
This article presents triathlon as a modern form of sports consumption. The theoretical part underlines the importance of triathlon events for the development of tourism and the promotion of health and physical activity, whereas the empirical part presents the results of research carried out at the Środa Wielkopolska Triathlon 2018 event. The socio-demographic profile of the participants of the event (N=109) and their motives for participation were determined. The information contained may be of value for those involved in the development of sport and tourism in smaller towns in Poland.